Barriers To Learning English Banyuwangi Marine Academy Students - Doni Hadi Irawan; Muhamad alfi khoiruman (JURNAL ILMU PENDIDIKAN (JURIP), 2022)
English is one of obligatory subjects given in Junior High School and Senior High School. At university level, English is also given as the main goal of this class is to prepare the grads to face global competition. The research aimed to describe English learning problems reported by the learners as non – English Department students. This study applied qualitative research method and use observation and data recording, as the instruments. The data were analyzed through three stages: data reduction, data display, and conclusion drawing/verification. The results of the study show that students experience a range of English learning problems. It happened due to different proficiency level of the students.